1996
DOI: 10.1111/j.1476-5381.1996.tb15194.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity studies of mast cell activation and hypotension induced by neuropeptide Y (NPY), centrally truncated and C‐terminal NPY analogues

Abstract: 1 Neuropeptide-induced histamine release is thought to occur via receptor-independent mechanisms, with net charge and lipophilicity being important factors. 2 In this study, the histamine releasing ability of neuropeptide Y (NPY), two C-terminal segments of NPY and 13 centrally truncated NPY analogues was examined. These results were compared with the ability of the peptides to bind to the Y2 receptor in the rabbit kidney membrane model and with their hypotensive actions in the anaesthetized-rat model. 3 All a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…[86][87][88][89] Several neuropeptides (eg, SP, VIP, and neuropeptide Y) can bind to and activate mast cells, resulting in degranulation and histamine release. [90][91][92] Furthermore, Ansel and coworkers 93 demonstrated that mast cell TNF-␣ mRNA is selectively upregulated by SP in a dose-dependent manner. Substance P increased TNF-␣ secreted from cloned murine mast cells and freshly isolated peritoneal mast cells.…”
Section: Mast Cellsmentioning
confidence: 99%
“…[86][87][88][89] Several neuropeptides (eg, SP, VIP, and neuropeptide Y) can bind to and activate mast cells, resulting in degranulation and histamine release. [90][91][92] Furthermore, Ansel and coworkers 93 demonstrated that mast cell TNF-␣ mRNA is selectively upregulated by SP in a dose-dependent manner. Substance P increased TNF-␣ secreted from cloned murine mast cells and freshly isolated peritoneal mast cells.…”
Section: Mast Cellsmentioning
confidence: 99%
“…Although peptides 35−37 were improved with respect to Y 2 receptor selectivity against the Y 1 or the Y 5 receptor, the Y 2 receptor affinity was lower compared to peptide 28 and 29, with peptide 37 being the best with a Y 2 receptor binding of 2.0 nM and potency of 7.6 nM. This could be slightly improved to 1.3 nM (binding) and 2.0 nM (potency) if Ser 3 and Ile 28,31 in NPY were replaced with Ile 3 , Leu 28 , and Val 31 in PYY, as represented by peptide 38, but the achieved selectivity versus the other receptors was lower than for peptides 28 and 29. A more recent truncated analogue, Abz-PYY 25−36 14 (34), notably displayed very increased selectivity against the Y 1 and Y 5 receptor, with a ratio of Y 1 /Y 2 and Y 5 /Y 2 of approximately 2500 and 650.…”
Section: ■ Resultsmentioning
confidence: 96%
“…The potency of [Trp 30 ]PYY 3−36 (27) follows that of the binding data with equal Y 2 receptor potency as PYY 3−36 but increased selectivity toward the Y 1 receptor of approximately 50-fold, however, with no improvement in Y 5 receptor selectivity. By combining Trp 30 with either MeArg 35 or β-homoArg 35 , we obtained two analogues [Trp 30 ,MeArg 35 ]-PYY 3−36 (28) and [Trp 30 ,β-hArg 35 ]PYY 3−36 (29), that showed even greater selectivity than the analogues with one substitution while good Y 2 receptor affinity and potency were maintained. For the analogue [Trp 30 (29), modest improvement in selectivity and Y 2 receptor affinity was observed for the combination of Trp 30 and β-hArg 35 (Table 4).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations